1990
DOI: 10.1093/ndt/5.suppl_1.165
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Computer-Modulated Profile Haemodialysis on Cardiac Arrhythmias

Abstract: To reduce hamodialysis-induced ventricular arrhythmias, each of 15 patients (age 66.9 +/- 6.2 years) with end-stage renal disease and cardiac irregularities was treated subsequently with four different computer-modulated bicarbonate haemodialysis profiles (A-D) for 2 weeks respectively: (A) constant UF, dialysate Na (138 mmol/l) and K (2 mmol/l); (B) decreasing UF, otherwise as (A); (C) decreasing UF and Na (starting with 10% higher than serum Na), otherwise as (A); (D) decreasing UF and Na, adapted K to achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…Several groups of investigators have found the hemodialysis treatment itself to increase the rate of ventricular ectopy (103–106), although others note no such increase (107–109). Among those who have observed increased ectopy, the majority find a relationship with dialysis‐induced reductions in S K (103,110–112), although, again, this is not universally found (105). Serious dialysis‐related arrhythmias have been independently associated with underlying coronary artery disease (105,106), left ventricular hypertrophy and digoxin use (103), systolic blood pressure (109), and advanced age (105,109).…”
Section: Treatment Of Hyperkalemia In Esrdmentioning
confidence: 99%
“…Several groups of investigators have found the hemodialysis treatment itself to increase the rate of ventricular ectopy (103–106), although others note no such increase (107–109). Among those who have observed increased ectopy, the majority find a relationship with dialysis‐induced reductions in S K (103,110–112), although, again, this is not universally found (105). Serious dialysis‐related arrhythmias have been independently associated with underlying coronary artery disease (105,106), left ventricular hypertrophy and digoxin use (103), systolic blood pressure (109), and advanced age (105,109).…”
Section: Treatment Of Hyperkalemia In Esrdmentioning
confidence: 99%
“…Headache, cramps, fatigue, nausea, arterial hypertension and cardiac arrhythmias [1,10,11] are the main compli cations seen in patients subjected to extracorporeal ace tate haemodialysis and less frequently with bicarbonate dialysis. Although the underlying mechanisms are not always quite clear, uraemic disorders of the autonomic nervous system [5], volume depletion [1,3], fluid shifts from the extra-to the intracellular space [9] and steep, transmembraneous potassium gradients [10] have been shown to account for these complications. Hence, com puter-modulated profile haemodialysis was designed to prevent these side-effects [11].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the simultaneous study of cardiac arrhythmias [10], only patients with proven coronary heart disease were selected. The study had the approval of the Ethics Committee of the University of Marburg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,6,11,13,19]. der Plasma-Ionenkonzentrationen, des Säure-Basen-Haushalts, des volämischen Zustandes und hämodynamischer Größen.…”
unclassified